Negation of Universalist Ontology as the Basis for the Conceptualization of the “Postmarxism” Concept - Шелудченко, Ігор (Idei (Sofiâ.), 2020)
The article addresses the problem of etymological and theoretical uncertainty of the “postmarxism” concept, which is traced in both domestic and specialized Western studies. The basis for the formation of mental constructs, in the direction of clarifying the specifics of postmarxism, is its setting on “overcoming metaphysics”, which is expressed in an actual refusal to decode social phenomena / processes through the reference to their basic values. The study identifies the main theoretical and methodological contradictions in the understanding of postmarxism, and at the same time, in order to confirm the subject of the work, attention is paid to the avoidance of contradictions and oppositions by postmarxism itself. Because any opposition in postmarxism is questionable, it is a prerequisite for superstructure, which is meaningless itself. Also, a theoretical-comparative and semantic analysis of the "postmarxism” concept is conducted, the historical-political context of the evolution of the concept as a theoretical category and as self-identification is analyzed in order to define its position by some philosophers. The background to its formation is fundamental to explain the denial of universal ontology in postmarxism. Namely, they are decentralization, “breaking up” of structure, derriadian critique of the transcendental meaning, which in postmarxism is expressed as an artificial fixation of meaning and “ideological arrangement”.